Effects of Sevoflurane Anesthesia on Cerebral Lipid Metabolism in the Aged Brain of Marmosets and Mice - Mao, Haoli; Zhu, Jiao; Cheng, Yanyong; Shi, Lingling; Chen, Xiao; Zhou, Ren; Xue, Zhenyu; Liu, Siyu; Qiu, Zilong; Jiang, Hong (Frontiers in Molecular Neuroscience, 2022)
Objective In the lipid-rich brain, lipids performed signaling processes associated with the control system of the cell cycle, stress, and inflammatory reactions, as well as maintained brain and cellular homeostasis. The effects of general anesthesia on brain impairment in the elderly were controversial and complex. The study sought to evaluate the effect of lipid metabolism in the brain of aged marmosets and mice under long-term exposure to sevoflurane. Methods A total of 6 marmosets over 8-year-old and 10 mice aged 18 months were divided into the sevoflurane anesthesia and control groups, respectively. Marmosets in the sevoflurane anesthesia group were exposed to 1.5–2.5% sevoflurane and 100% O2 for 6 h. Mice anesthetized with sevoflurane were exposed to 3% sevoflurane and 60% O2 for 6 h. All prefrontal cortex tissues of marmosets and mice were harvested for the analysis of lipidomics. Results Compared to the control group, we found that phosphatidylethanolamine (PE) (18:0/22:5), PE (16:0/22:5), PE (18:2/22:5), PE (14:0/22:5), and PE (18:1/22:5) increased in the prefrontal cortex of marmosets in the sevoflurane group, while triglyceride (TAG)56:5-fatty acid (FA) 20:4, TAG58:10-FA22:6, and TAG60:10-FA22:6 decreased. For aged mice, we indicated that lipid components phosphatidic acid (PA) (18:1/20:2) and TAG52:5-FA20:4 in the sevoflurane group increased, but PE (14:0/22:4), diglyceride (DAG) (16:1/18:2), and lysophosphatidylcholine (LPC) (16:1) + AcO decreased. More deeply, sevoflurane anesthesia resulted in the presence of 70 specific lipids in mice and marmosets. The enriched lipid subclasses were mainly monoacylglycerophosphoethanolamines and five other subclasses. Conclusion Sevoflurane caused slight changes in lipid metabolism both in the aged brain of marmosets and mice. However, the pathways of lipid metabolism were not affected. The effects of sevoflurane on lipid metabolism in aged brains may differ among species.